PENGARUH PENAMBAHAN ALGINAT TERHADAP KUALITAS BAKSO IKAN TODAK (Tylosurus crocodilus) - Sahrul Diansyah; Jumsurizal Jumsurizal; Reno Irwanto; Sri Novalina A (Fisheries Product Technology Department, Faculty of Marine Science and Fisheries, Universitas Maritim Raja Ali Haji, 2023)
Meatballs are one of the most popular foods in today's society. Basically, the term meatball is followed by the name of the type of meat, such as: One of them is alginate. In this study, there were first his four normal or control treatments (F0) and (F1, F2, F3, F4), with different formulations of wheat flour and alginate addition. The purpose of this study was to find the optimal formulation of alginate-enhanced swordfish balls to produce fish balls that are nutritious and safe for consumption. As a result of the investigations carried out, the F3 sample was the best value given by the panelists and the approximate test results for the F3 treatment were 66.24% moisture content, 10.53% fat content and 2.21% ash content. became clear. 9.09% protein content, 0.12% carbohydrates. The texture profile analysis test results were a hardness value of 1060, adhesion of 27.99, cohesion of 0.70 and resilience of 50.0. The calculated nutrient adequacy (RDA) is 0.032 for carbohydrate, 14.66 for protein and 11.57 for fat.